Self-management versus usual care for greater trochanteric pain syndrome (the HIPS trial): study protocol for a randomised controlled trial - Michael Skovdal Rathleff; Are Hugo Pripp; Jens Ivar Brox; Britt Elin Øiestad; Marianne Bakke Johnsen; John Bjørneboe; Niels Gunnar Juel; Rikke Munk Killingmo; Kaia B Engebretsen; Thea Morin Melås; Maren Lunder Wefring; Sigrid Skatteboe; et al. (BMJ Open)
Introduction Greater trochanteric pain syndrome (GTPS) is a common and disabling condition characterised by lateral hip pain. The condition often persists for several months, and there is low evidence for any superior treatment. The aim of this study protocol is to describe a randomised controlled trial (RCT) investigating the effectiveness of a self-management programme versus usual care for patients with GTPS.Methods and analysis The study is designed as an observer-blinded, parallel group, superiority RCTcomparing a self-management programme (n=55) with usual care (n=55). Eligible patients with GTPS will be included based on reproduction of pain on palpation in the greater trochanteric region and at least one positive clinical provocation test. The self-management programme includes 3–5 individual sessions with a physiotherapist over 12 weeks, addressing physical, emotional and behavioural factors deemed relevant by the patient. Usual care will receive general information about GTPS, activity management and are free to seek further treatment in primary care as wanted. The primary outcome measure is the Norwegian version of the Victorian Institute of Sports Assessment for gluteal tendinopathy questionnaire (VISA-G-Norwegian). Outcomes will be assessed at baseline, 3, 6 and 12 months. A longitudinal mixed effects model will be used to assess the effectiveness of treatment on pain and disability across all time points, with the primary endpoint at 6 months. Cost-effectiveness will be expressed by mean incremental cost-effectiveness ratios (ICERs) from a societal and healthcare perspective. Bootstrapping will be used to estimate ICER uncertainty.Ethics and dissemination The Norwegian Regional Committees for Medical and Health Research Ethics have approved the project (2023/590816), and it will be in accordance with recommendations from the Data Inspectorate at Oslo University Hospital (22/26396). The results from the study will be disseminated through publications in peer-reviewed journals, in conference presentations and through the user representative.Trial registration number NCT06297148.